Risk based assessment of subsynchronous resonance in AC/DC Systems - Adrees, Atia (Springer Verlag, 2016)
This relevant and timely thesis presents the pioneering use of risk-based assessment tools to analyse the interaction between electrical and mechanical systems in mixed AC/DC power networks at subsynchronous frequencies. It also discusses assessing the effect of uncertainties in the mechanical parameters of a turbine generator on SSR in a meshed network with both symmetrical and asymmetrical compensation systems. The research presented has resulted in 12 publications including three top international journal papers (IEEE Transactions on Power Systems) and nine international conference publications, including two award-winning papers. .
Keywords: Electric power system stability -- Mathematical models.; Electric power transmission -- Direct current.; Electric power transmission -- Alternating current.; elektronické knihy; electronic books